2019
DOI: 10.1002/anie.201902470
|View full text |Cite
|
Sign up to set email alerts
|

De novo Design of Selective Membrane‐Active Peptides by Enzymatic Control of Their Conformational Bias on the Cell Surface

Abstract: Selectively targeting the membrane-perturbing potential of peptides towards ad istinct cellular phenotype allows one to target distinct populations of cells.W ereport the de novo design of an ew class of peptide whose ability to perturb cellular membranes is coupled to an enzyme-mediated shift in the folding potential of the peptide into its bioactive conformation. Cells rich in negatively charged surface components that also highly express alkaline phosphatase,f or example many cancers,a re susceptible to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…A prominent difference between iPSCs and differentiated cells is that iPSCs overexpress (or upregulate) alkaline phosphatase (ALP), but the differentiated cells do not. Thus, it is possible to selectively kill iPSCs by using enzyme-instructed self-assembly (EISA), a molecular process that integrates enzyme reactions and self-assembly and is known to selectively kill cells based on overexpression of enzymes. , In fact, Saito et al recently reported selectively eliminating iPSCs by EISA of d -phosphotetrapeptides . Taking the advantage that ALP acts as an ectophosphatase to form pericellular nanofibers of d -peptides, they have shown that ALP overexpressed on iPSCs dephosphorylates the d -phosphotetrapeptides (e.g., 1 ) into hydrophobic peptides, which self-assemble on the cell surface to induce cell death.…”
Section: Introductionmentioning
confidence: 99%
“…A prominent difference between iPSCs and differentiated cells is that iPSCs overexpress (or upregulate) alkaline phosphatase (ALP), but the differentiated cells do not. Thus, it is possible to selectively kill iPSCs by using enzyme-instructed self-assembly (EISA), a molecular process that integrates enzyme reactions and self-assembly and is known to selectively kill cells based on overexpression of enzymes. , In fact, Saito et al recently reported selectively eliminating iPSCs by EISA of d -phosphotetrapeptides . Taking the advantage that ALP acts as an ectophosphatase to form pericellular nanofibers of d -peptides, they have shown that ALP overexpressed on iPSCs dephosphorylates the d -phosphotetrapeptides (e.g., 1 ) into hydrophobic peptides, which self-assemble on the cell surface to induce cell death.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CPPs could perturb membranes and become membrane permeabilizers at high concentrations, , thus leading to rapid necrosis of cancer cells through membrane lysis . Given the lytic functions of cationic polypeptides, we studied the cytotoxicity effects of drug-free ETCPP dendrimers (Table ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Published in 2019, Junfeng Shi and Joel Schneider de novo designed a peptide, DVP-1P that is unfolded until it interacts with alkaline phosphatase (ALP), an enzyme that is overexpressed on the surface of some cells including cancer cells [ 95 ]. When the peptide interacts with ALP it causes a conformational shift leading to “cell-surface-induced folding” which can perturb and, in high concentration, lyse the cell membrane.…”
Section: Design Of Protein Interfacesmentioning
confidence: 99%